Hermite-Hadamard inequality involving Caputo-Fabrizio fractional integrals and related inequalities via s-convex functions in the second sense - Anjum Mustafa Khan Abbasi; Matloob Anwar (AIMS Mathematics, 2022)
In this paper, firstly, Hermite-Hadamard inequality via s-convex functions in the second sense using Caputo-Fabrizio fractional integral operator is established. We also compare our results with the existing ones. It is also shown that the obtained results are a generalization of the existing results. Finally, we give their applications to special means.